Pengembangan Rencana Pelaksanaan Pembelajaran Berbasis Kearifan Lokal dengan Model Problem Based Learning (PBL) pada Materi Usaha dan Pesawat Sederhana di SMPN Kota Jambi - M. Habibie; Rayandra Asyhar; Bambang Hariyadi (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to develop a local wisdom-based learning implementation plan for businesses and simple machines. The lesson plan is a tool used by teachers to carry out learning inside or outside of school. The development model used is the 4D development model, which consists of define, design, develop, and disseminate stages. and disseminate. This local wisdom-based learning tool can be used as a problem context to explore science concepts, especially in junior high schools. RPP media expert validation got a maximum score of 72 out of 90 and was in the interval 76–90 with the category